The Influence of Job Performance Assessment on Employee Motivation and Compensation as Intervening Variables in TNI Members in Denhubrem, Palembang City - Yoga Juliantara; Fretty Welta (Entrepreneurship Faculty, Universitas Garut, 2022)
The purpose of this study was to determine the effect of work performance appraisal variables on employee motivation and compensation as an intervening variable for members of the TNI at the Denhubrem, Palembang City. The results of work performance appraisal can affect employee motivation. Motivation influences human behavior and is hard, so they want to work hard and are eager to achieve optimal results. In addition, compensation affects employee motivation. This research uses the path analysis method to prove that the compensation variable can mediate between work performance appraisal and work motivation. The direct and indirect effect of work performance appraisal on work motivation is calculated.